The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1111/j.2047-2927.2012.00031.x
|View full text |Cite
|
Sign up to set email alerts
|

Seminal, ultrasound and psychobiological parameters correlate with metabolic syndrome in male members of infertile couples

Abstract: SUMMARYMetabolic syndrome (MetS) is a diagnostic category which identifies subjects at high risk for diabetes and cardiovascular diseases, erectile dysfunction (ED) and male hypogonadism. However, MetS impact on male infertility has been poorly studied. We systematically evaluated possible associations between MetS and clinical characteristics in men with couple infertility. Out of 367 consecutive subjects, 351 men without genetic abnormalities were studied. MetS was defined according to the International Diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 72 publications
(99 reference statements)
7
53
2
1
Order By: Relevance
“…We may speculate that several factors might account for these differences. Emphasis on obesity when defining MetS (such as the case of Lotti et al 22. using the International Diabetes Federation worldwide definition) and older age (as observed in our secondary infertile patients) might unveil the impact of MetS on seminal parameters whereas younger age and NCEP-ATP III definition, as observed in our sample of primary infertile men, would not 34…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…We may speculate that several factors might account for these differences. Emphasis on obesity when defining MetS (such as the case of Lotti et al 22. using the International Diabetes Federation worldwide definition) and older age (as observed in our secondary infertile patients) might unveil the impact of MetS on seminal parameters whereas younger age and NCEP-ATP III definition, as observed in our sample of primary infertile men, would not 34…”
Section: Discussionmentioning
confidence: 73%
“…We found that tT was reduced in +MetS patients compared to the –MetS group whereas cfT did not seem to be affected by this condition. In contrast, Lotti et al 22. reported decreased values of both tT and fT, while Leisegang et al 23.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Standardized protocols with axial and transverse examinations of the lesions were performed (Oyen, 2002, Bhatt et al ., 2006; American Institute of Ultrasound in M edicine et al . 2011; Lotti et al ., 2013). Two experienced sonographers (A.M.I.…”
Section: Methodsmentioning
confidence: 99%